Chemical reaction technology - Murzin, Dmitry, 1963- (De Gruyter graduate., 2015)
The book discusses the sciences of operations, converting raw materials into desired products on an industrial scale by applying chemical transformations and other industrial technologies. Basics of chemical technology combining chemistry, physical transport, unit operations and chemical reactors are thoroughly prepared for an easy understanding.